Cervical spine injuries in Poland – epidemiology, divisions, and causes - Wolan-Nieroda, Andżelina; Maciejczak, Andrzej; Guzik, Agnieszka; Przysada, Grzegorz; Wyszyńska, Justyna; Szeliga, Ewa (European Journal of Clinical and Experimental Medicine, 2017)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of the study was to review the literature on the prevalence of cervical spine injuries divided between the level of the injury and the causes of fractures. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A review of Polish and foreign literature was performed. The following databases were searched: PubMed, Medline, Science Direct, Termedia, and Polish Medical Bibliography. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Literature analysis. In Poland the incidence of spinal injuries, including damage to the cord, is estimated at the level of 25–35 persons per one million of the population, half of these being cervical spine injuries. More than one in three of all spinal injuries affect the atlantoaxial and occipital area. It is estimated that axis fractures occur in up to 40% of the cases involving cervical spine injury. Odontoid fractures constitute 10–15% of all cervical spine fractures. Hangman fractures account for 20% of vertebral fractures. Cervical spine injuries more frequently occur in males than in females, and the relevant rates for males are from 1.5 to 2.7 times higher. The most common causes of cervical spine injuries include road traffic accidents, accounting for 33 to 75% of the cases, falls from heights (15–44%) and sports injuries (4–18%). Cervical spine injuries are most often diagnosed in subjects over thirty years of age. Such injuries most commonly are related to the second, fifth and sixth cervical vertebrae. On the other hand damage to the first and second cervical vertebrae is often observed in the same patients who are found with injury to lower cervical vertebrae (approx. 9% of the cases). In the group of advanced age subjects the most frequent cervical spine injuries are axial fractures and they are diagnosed in 15% of adult patients with cervical spine fractures.